Identifikasi Entomopatogen Bakteri Merah pada Wereng Batang Coklat (Nilaparvata lugens Stål.) - Tri Puji Priyatno; Yohana A Dahliani; Yadi Suryadi; I Made Samudra; Dwi Ningsih Susilowati; Iman Rusmana; Baskoro S Wibowo; Cahyadi Irwan (Jurnal AgroBiogen, 2011)
Indentification of Entomopathogenic Red Bacterial fromBrown Planthopper (Nilaparvata lugens Stål.). Tri P.Priyatno, Yohana A. Dahliani, Yadi Suryadi, I MadeSamudra, Dwi N. Susilowati, Iman Rusmana, Baskoro S.Wibowo, and Cahyadi Irwan. Red bacteria isolated frombrown planthopper (BPH) has been proven pathogenicagainst BPH and others insects. Application of 106 to 107cells/ml of red bacteria caused 65.6-78.2% mortality of BPH.The 50% effective concentration (EC50) and lethal time of redbacteria against BPH is 2.8 x 105 cells/ml and 6.8 days,respectively. Based on phenotypic characters tested on GNMicroPlateTM Biolog kit and 16S rRNA sequneces analysis,red bacteria was identified as Serratia marcescens with 99%similarity. Red pigmen produced by S. marcescens strainBPH is secondary metabolite determined as prodigiosinshowing bactericidal activities against Xanthomonas oryzaepv. oryzae. We concluded that S. marcescens did not onlypotent as biocontrol agent to BPH, but also it can be used tocontrol plant pathogenic bacteria.